Inégalités et discrimination: les migrants pendant et après la pandémie de Covid Inequalities and discrimination: migrants during and after the Covid pandemic - Giacalone, Fiorella (EtnoAntropologia, 2023)
The text reflects on the forms of discrimination that the concept of nation, with the idea of a hypothetical national purity, creates towards foreigners and non-citizens. Institutional racism arises as a legal-social sphere that prevents the foreigner from obtaining social and political rights. This is why anthropologists continue to deconstruct the discursive practices that define an essentialist vision of culture tending to create a reification of differences. The Covid-19 pandemic has worsened the situation of migrants, especially in terms of employment, increasing forms of inequality.